The effectiveness of a phonological-based intervention for students in their first year of school : a thesis presented in partial fulfilment of the requirements for the degree of Master of Literacy Education at Massey University, Hokowhitu, New Zealand - Wild, Sarah Anne (Massey University, 2012)
New Zealand has a long tail of underachievement in reading with the results of international literacy surveys consistently showing that while some New Zealand students are among the best readers in the world, the gap between the best and poorest readers continues to widen. Research evidence indicates that a potential reason for the increasingly large gap is a lack of focus on the explicit teaching of phonologically-based decoding skills in the early years of school. The purpose of this study was to first determine the levels of alphabet knowledge and phonological awareness in a group of students at school entry and compare these levels to a group of slightly older students also in their first year of school. A second aim was to evaluate the efficacy of a nine-week explicit intervention that targeted phonologically-based skills for improving decoding ability. This study is a modified replication of a study conducted by Greaney and Arrow (2012). The study is a non-randomised, pretestintervention- posttest design with one control group. A total of 30 students were included in the study. The intervention group involved a new entrant class while the control group involved a year one class. All students were assessed using a range of phonologically-based assessments. The intervention group received the intervention in addition to their regular literacy programme while the control group only received their regular literacy programme. The results showed that the students within the intervention group entered school with a range of phonological awareness and alphabet knowledge. A key finding was that the students who had received the intervention significantly outperformed the control group on two measures of isolated decoding (the Burt word reading test and pseudoword reading) when pretest letter sound knowledge was controlled. The results of this study highlight the importance of using phonologically-based assessments with students as soon as they start school in order to identify those at risk and plan effective programmes to meet the needs of these students.
Keywords: New Zealand literacy; Reading in primary school; Emergent literacy; Phonologically-based reading; Literacy programmes